2021
DOI: 10.1088/1361-6463/ac0bd8
|View full text |Cite
|
Sign up to set email alerts
|

A hybrid plasma de-icing actuator by using SiC hydrophobic coating-based quartz glass as barrier dielectric

Abstract: Aircraft icing poses a major threat to flight safety, and plasma anti-/de-icing becomes a new approach in the field of anti-/de-icing in recent years. In this paper, a surface dielectric barrier discharge (SDBD) plasma actuator with SiC hydrophobic coating-based quartz glass is designed and fabricated. Actuated by nanosecond high voltage pulse, its de-icing characteristics are explored experimentally and compared with the uncoated actuator. The results show that under the same actuation parameters, the dischar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…The authors concluded that the combination of NS-DBD plasma actuation and SHS coating effectively prevents ice accretion on the entire structure of the airfoil. Actuator surface wettability was also addressed in the study by Zheng et al [181], where the effect of a hydrophobic coating on the dielectric layer of a SDBD plasma actuators was studied. Two types of dielectric layers were prepared, one of ordinary quartz (1 ± 0.01 mm thick) and another of SiC treated quartz glass, both with exposed electrodes (5 × 50 mm) and buried electrodes (15 × 40 mm) in copper foil (0.03 mm thick) arranged in an asymmetric configuration.…”
Section: Plasma Actuators For Deicing and Ice Formation Preventionmentioning
confidence: 99%
“…The authors concluded that the combination of NS-DBD plasma actuation and SHS coating effectively prevents ice accretion on the entire structure of the airfoil. Actuator surface wettability was also addressed in the study by Zheng et al [181], where the effect of a hydrophobic coating on the dielectric layer of a SDBD plasma actuators was studied. Two types of dielectric layers were prepared, one of ordinary quartz (1 ± 0.01 mm thick) and another of SiC treated quartz glass, both with exposed electrodes (5 × 50 mm) and buried electrodes (15 × 40 mm) in copper foil (0.03 mm thick) arranged in an asymmetric configuration.…”
Section: Plasma Actuators For Deicing and Ice Formation Preventionmentioning
confidence: 99%
“…The anti-icing ability became stronger with an increase in the water content.Liu et al and Wei et al [ 15 , 16 ] found that the instantaneous value of the discharge voltage and the oscillation of the current curve decrease when water drop-lets strike the surface of the SDBD actuator. Zheng et al [ 17 ] found that when droplets collide with an SDBD surface, the air and electrodes are fully protected by water. Therefore, the discharge was inhibited, and the inhibition area gradually expanded with increasing discharge time.…”
Section: Introductionmentioning
confidence: 99%